PELATIHAN PEMBUATAN MEDIA FOTONOVELA MENGGUNAKAN APLIKASI PORTABLE BAGI GURU SD - Ratna Widyaningrum, Ema Butsi Prihastari & (Widya Wacana: Jurnal Ilmiah, 2016)
The development of information and communication technology is simultaneous witheducation in Indonesia. The material taught is not interesting if it is only what it is in thetextbooks. Learning resources for primary education should be presented by using the mediathat invites the students to get closer to the environment. The use of the image to explain thecontent of the material is one of the alternatives. The Purpose of this community serviceprogram was to deliver insight and skill like portable application usage such as Flip BookMaker and Comic Life for creating photonovela media to elementary school teachers. Thisoutreach was conducted at SDN Prawit I no. 69. The method of implementation of communityservice include: 1) preparation, 2) implementation of training includes the presentation of thematerial, practice assignments, evaluation activities, and reflection and closure activities.External Targets expected are primary school teachers who follow the making of photonovelamedia training can apply them yourself on the material to be taught to learners, and todocument them in the form of a CD to be used to teach the next. Teachers who attend trainingcan adjust in accordance with the most recent knowledge developments.Keywords: media, photonovela, portable applications